PENGELOLAAN MANAJEMEN KEARSIPAN DI PERGURUAN TINGGI - Ermawaty, Ermawaty (TABULARASA, 2013)
Filing are a memory centre, resources, a surveillance tool that is indispensable in any organization in order to carry out any activities. The activities either in the offices of State Institutions, Private and colleges. In addition to the archive is a very important instrument in an institution that needs to be maintained, cared for and well done management in order to be useful and utilized at a later date. College as an educational institution has the administrative and academic documents. As an institution of the most widely produced documents and academic administration, it is necessary to safeguard against these documents. Therefore universities need to establish archival work unit manager, recruiting manager/ archivist who has competence in the field of archives, archival inventory soon that a high use value, historical archives and archival institutions and archival research papers, college leaders hoped the policy to expand its activities to support the advancement of archives in records management.